2014
DOI: 10.1021/cg401715e
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Flow Tubular Crystallization in Slugs Spontaneously Induced by Hydrodynamics

Abstract: A novel continuous crystallizer design is described with the potential to provide improved control of crystal properties, improved process reproducibility, and reduced scale-up risk. Liquid and gas are introduced into one end of the tube at flow rates selected to spontaneously generate alternating slugs of liquid and gas that remain stable while cooling crystallization occurs in each liquid slug. Mixing within each stable self-circulating slug is maximized by controlling the slug aspect ratio through specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
192
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(196 citation statements)
references
References 28 publications
4
192
0
Order By: Relevance
“…However, studies often focused on components with relatively fast nucleation kinetics [2,5,7,10]. This leaves the nucleation of molecules with slow nucleation kinetics as one of the key challenges for tubular crystallizers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies often focused on components with relatively fast nucleation kinetics [2,5,7,10]. This leaves the nucleation of molecules with slow nucleation kinetics as one of the key challenges for tubular crystallizers.…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge is fouling, which eventually leads to clogging. Whilst multiple solutions to fouling are suggested in literature, they often add a lot of complexity and can only limit fouling to a certain degree [10,13,14]. A general rule to minimize fouling is to work at low supersaturations; however, this decreases nucleation rates even more, highlighting the need to enhance nucleation at low supersaturations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a parent crystal or tablet is fixed on a rotating shaft. Seed crystals [34,35] Liquid-liquid slug flow…”
Section: State Of the Artmentioning
confidence: 99%
“…Seed crystals of paracetamol were subsequently grown in a tubular growth section [31,32]. In order to minimize axial dispersion [33,34] and to prevent clogging of tubular devices [34], the application of a gas-liquid slug flow is under investigation for continuous cooling crystallization. Jiang et al reported on a slug-flow device which was used as a growth section for the L-asparagine monohydrate (water) system.…”
Section: State Of the Artmentioning
confidence: 99%
“…Thus, an efficient particle fluidization is crucial for robust operation. Pulsating flow by piston movement (e.g., COBC) [47] and gas-liquid slug flow [95][96][97] is under discussion to facilitate particle transport in plug flow crystallization. For helically coiled tubes, there is evidence that Dean vortices enhance particle fluidization and reduce scaling of surfaces, e.g., in membrane filtration processes [100].…”
Section: Coiled Flow Inverter For Crystallizationmentioning
confidence: 99%